2013
DOI: 10.1017/s0022215113000601
|View full text |Cite
|
Sign up to set email alerts
|

Acquired cholesteatoma: summary of the cascade of molecular events

Abstract: The role of lipids in this disease is relatively unexplored, but there is evidence in support of fatty acid role-players that needs confirmation. Future directions in lipid research to delineate molecular mechanisms are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 65 publications
0
23
0
1
Order By: Relevance
“…LPS stimulates osteoclastogenesis directly from mononuclear osteoclast precursors. Furthermore, it stimulates production of interleukin (IL)-1β, IL-6, prostaglandin (PG) E2, and tumor necrosis factor alpha (TNF-α) from macrophages and monocytes with resultant increase in inflammatory activity [8,61-65]. Jung et al [66] performed an experimental study to investigate the role of PA in the aggressiveness of induced cholesteatoma in gerbils and found that infected cholesteatomas showed more expansion and became more aggressive than uninfected control subjects.…”
Section: Mechanisms Of Bone Resorption In Cholesteatomamentioning
confidence: 99%
See 1 more Smart Citation
“…LPS stimulates osteoclastogenesis directly from mononuclear osteoclast precursors. Furthermore, it stimulates production of interleukin (IL)-1β, IL-6, prostaglandin (PG) E2, and tumor necrosis factor alpha (TNF-α) from macrophages and monocytes with resultant increase in inflammatory activity [8,61-65]. Jung et al [66] performed an experimental study to investigate the role of PA in the aggressiveness of induced cholesteatoma in gerbils and found that infected cholesteatomas showed more expansion and became more aggressive than uninfected control subjects.…”
Section: Mechanisms Of Bone Resorption In Cholesteatomamentioning
confidence: 99%
“…The progressive bone erosion made by cholesteatoma can lead to permanent hearing loss, vestibular dysfunction, facial palsy, and more fatal intracranial complications [7]. It was found that a complex process with integration of both molecular and cellular events could play the major role in cholesteatoma formation, growth as well as its destructive pattern [1,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…In the perimatrix of acquired cholesteatoma, there is inflammatory cell infiltration such as lymphocyte and polymorphonuclear cells. [12][13][14] Acute inflammation is triggered by events such as bacterial or viral infections, trauma, tissue necrosis, and immune reactions. T lymphocytes play a greater role in the response of the body to viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, Louw reviewed the role of microorganism-induced alterations in lipid metabolism in matrix cell apoptosis and cholesteatoma deterioration. 17 It is therefore likely that fungal elements associated with cholesteatoma play a significant role in the disease progression. The major goal of cholesteatoma surgery is to completely remove keratin and matrix debris from the middle-ear cleft to achieve a safe, stable ear.…”
Section: Discussionmentioning
confidence: 99%